The Importance of ANEFRO in the Prevention of Urolithiasis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This article presents the results of a study conducted on patients with urolithiasis. In the study, the results of examination and treatment of patients with complicated and uncomplicated types of urolithiasis of different ages and genders, as a result of Anefro drug alone and in combination with other drugs, are presented. The results of the study showed positive results for patients in all groups, both when using the anefro drug alone and when using it in combination. There were no side effects, exacerbation of diseases and development of complications in patients.